Damage control resuscitation: how it’s done and where we can improve. A view of the Brazilian reality according to trauma professionals - MARCELO AUGUSTO FONTENELLE RIBEIRO JUNIOR; LETICIA STEFANI PACHECO; JUAN CARLOS DUCHESNE; JOSE GUSTAVO PARREIRA; SHAHIN MOHSENI (Revista do Colégio Brasileiro de Cirurgiões)
ABSTRACT Introduction: Hemorrhage is the leading cause of preventable deaths in trauma patients, resulting in 1.5 million deaths annually worldwide. Traditional trauma assessment follows the ABC (airway, breathing, circulation) sequence; evidence suggests the CAB (circulation, airway, breathing) approach to maintain perfusion and prevent hypotension. Damage Control Resuscitation (DCR), derived from military protocols, focuses on early hemorrhage control and volume replacement to combat the “diamond of death” (hypothermia, hypocalcemia, acidosis, coagulopathy). This study evaluates the implementation of DCR protocols in Brazilian trauma centers, hypothesizing sub-optimal resuscitation due to high costs of necessary materials and equipment. Methods: In 2024, an electronic survey was conducted among Brazilian Trauma Society members to assess DCR practices. The survey, completed by 121 participants, included demographic data and expertise in DCR. Results: All 27 Brazilian states were represented in the study. Of the respondents, 47.9% reported the availability of Massive Transfusion Protocol (MTP) at their hospitals, and only 18.2% utilized whole blood. Permissive hypotension was practiced by 84.3%, except in traumatic brain injury cases. The use of tranexamic acid was high (96.7%), but TEG/ROTEM was used by only 5%. For hemorrhage control, tourniquets and resuscitative thoracotomy were commonly available, but REBOA was rarely accessible (0.8%). Conclusion: Among the centers represented herein, the results highlight several inconsistencies in DCR and MTP implementation across Brazilian trauma centers, primarily due to resource constraints. The findings suggest a need for improved infrastructure and adherence to updated protocols to enhance trauma care and patient outcomes.